Genomic-based transmission analysis of carbapenem-resistant Pseudomonas aeruginosa at a tertiary care centre in Cologne (Germany) from 2015 to 2020. Issue 3 (20th May 2022) - Wendel, Andreas F.; Malecki, Monika; Mattner, Frauke; Xanthopoulou, Kyriaki; Wille, Julia; Seifert, Harald; Higgins, Paul G.
Abstract: Objectives: To describe the propensity of carbapenem-resistant Pseudomonas aeruginosa to spread within a hospital critical care setting. Methods: The study was conducted in a 700-bed tertiary centre in Cologne, Germany. P. aeruginosa resistant to piperacillin, ceftazidime, cefepime, imipenem, meropenem and ciprofloxacin, isolated from clinical and screening specimens from four critical care units from 2015 to 2020 were analysed. Genotyping was carried out by WGS (Illumina and MinION). MLST, core genome MLST (cgMLST) and resistome analysis was performed and merged with epidemiological data. Results: Fifty-five out of 79 non-duplicate P. aeruginosa isolates were available, of which 20 were carbapenemase producers as follows: bla VIM-1 ( n = 1), bla VIM-2 ( n = 17), bla VIM-4 ( n = 1), and bla NDM-1 / bla GES-5 ( n = 1). Forty-two of 55 isolates were hospital-acquired. cgMLST revealed three clusters: Cluster 1 ( n = 15, ST111, bla VIM-2, recovered between 2015 and 2020); Cluster 2 ( n = 4, ST970, carbapenemase negative); and Cluster 3 ( n = 2, ST357, carbapenemase negative). The bla VIM-2 gene of Cluster 1 was integrated on the chromosome in a class 1 integron (type In59). Using conventional epidemiology, we were only able to confirm two patient-to-patient transmissions and one room-to-patient transmission on three different ICUs within Cluster 1. Isolates from Cluster 2 represented an outbreak occurring in 2019. Conclusions: These data give insight into the epidemiology of carbapenem-resistant P. aeruginosa . Transmission dynamics differed between carbapenemase- and non-carbapenemase-producing isolates. A continuous acquisition of clonally related ST111 VIM-2 P. aeruginosa, being the main carbapenemase-producing strain, was observed over the whole study period, as well as an overall higher genomic diversity among non-carbapenemase-producing P. aeruginosa .